The impact of gamification adoption intention on brand awareness and brand loyalty of Indonesian tourism industry from a tourist’s perspective - Joseph Julian Aslan; Daniel Tumpal Hamonangan Aruan (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Digital Transformation has affected the competitive landscape in this global environment. Many firms use technology to gain a competitive advantage in markets; one of the technologies used is Gamification, which is using a game to increase the intention or engagement of consumers in a marketing activity. Firms in Indonesia have also started using Gamification, such as Shopee or Gojek. Apparently, Gamification has also been used in Tourism Industry, though very scarcely and is still mostly in the development. Previous research has confirmed the positive impact of gamification adoption intention to brand awareness and brand loyalty from a marketer’s perspective. This research aims to confirm the same impact, however, from the perspective of customers/tourists. This research is done using data samples from roughly 200 Indonesian respondents of a 40-question online questionnaire with an Indonesian-themed game prototype as a stimulus and is analyzed using the PLS method. The result surprisingly shows that not every construct has positive impacts when viewed from the consumer’s point of view.